Evaluation of prices, availability and affordability of essential medicines in Lahore Division, Pakistan: A cross-sectional survey using WHO/HAI methodology - Saeed, Amna (PLoS One, 2019)
Inadequate access to medicines affected by un-controlled prices is a major concern in developing countries, including Pakistan, which lacks comprehensive data on medicine prices. Thus, the objective of this study was to evaluate the prices, availability and affordability of essential medicines in Lahore division, Pakistan. The survey was undertaken from November, 2016 till March, 2017 by including 50 medicines, 14 from the WHO/HAI core list and 36 supplementary medicines from national essential medicine list (NEML) at public (n = 16) and private (n = 16) health facilities. The prices, availability and affordability of selected medicines were measured using a variant of the WHO/HAI standard methodology available on HAI website and WHO/HAI manual. A questionnaire was used for data collection from Lahore division. The prices were compared to International reference prices (IRPs) and the daily wage of a lowest paid unskilled government worker was used to calculate medicine affordability. Data suggested poor availability of originator brands (OB) in public and private sector facilities, i.e., 6.8% and 55.0%, respectively. Similarly, low availability was observed for lowest price generics (LPGs), both in public (35.3%) and private sector (20.3%) facilities–far below the WHO global action plan targets of 80% availability of essential medicines by 2025. In private sector, 53% OB and 38% LPG medicines were found excessively priced. The cost of standard treatment with OBs was unaffordable, i.e., above a single daily wage (1.4 day’s wages) was demanded to purchase the standard treatment for the selected diseases in case of OBs medicines. Whereas, the cost of LPGs medicine required to purchase the standard treatment of the selected diseases was 0.6 day’s wage (median), below a single daily wage. In conclusion, access to essential medicines, especially at public sector facilities was affected by low availability, particularly of OBs in comparison to LPGs. Thus, the better availability of LPGs might be a rational basis of transition into a generic system of prescribing that may improve the availability and accessibility of essential medicines in Lahore division. Medicine prices in Lahore division were found higher in comparison to IRPs. Thus, the efforts must be made to formulate patient’s pocket friendly drug pricing policy that favors price cuts and improves affordability.